A meta‐analysis of the relationship between moral disengagement and bullying roles in youth. Issue 4 (21st March 2019) - Killer, Brittany; Bussey, Kay; Hawes, David J; Hunt, Caroline
Abstract: Over the last several years, researchers have become increasingly interested in the influence of moral factors on bullying behaviors. This is the first meta‐analytic review to exclusively examine the relationship between moral disengagement (MD) and the key bullying roles of bully, victim, defender, and bystander. Forty‐seven independent samples examining a total of 43, 809 children/adolescents (aged 7–19) were included in this meta‐analysis. Results indicated a positive relationship between MD and bullying ( r = 0.31; 95% CI [0.27, 0.34]), MD and victimization ( r = 0.08; 95% CI [0.05, 0.12]), and a negative relationship between MD and defending ( r = −0.11; 95% CI [−0.17, −0.04]). No significant relationship was found for MD and bystanding behavior. Moderators of bullying type (traditional vs. cyberbullying), reporting type (self vs. peer report), age, and gender were included in the analyses. The results are discussed in the context of relevant literature with particular emphasis on the importance of distinguishing between guilty and unconcerned bystanders, and the significant overlap between bullying and victimization in the cyber context.